KETERKAITAN ANTARA LEADER MEMBER EXCHANGE, PERCEIVED ORGANIZATIONAL SUPPORT, KOMITMEN AFEKTIF DAN KINERJA STUDI PADA KARYAWAN PT ADIKENCANA MAHKOTABUANA KEBAKKRAMAT KARANGANYAR - Asrori (Fakultas Ekonomi Universitas Pasir Pengaraian, 2016)
The purpose of this research was to investigates and analysis correlation betweenleader member exchange, perceived organizational support, affective commitment andperformance. The research focuses on employee performance PT AdikencanaMahkotabuana Kebakkramat Karanganyar. The study unitilizes probability samplingmethod and simple random sampling technique with 201 sample from 1.250 population. Byusing structural equational modeling analysis, the findings indicate that: (1) Leadermember exchange and affective commitment positive interaction on employee performancewith c.r value 3.198 ( 2) Leader member exchange and perceived organizational supportpositive interaction on affective commitment of employee with c.r value 4.294 and 7.503 ( 3)Perceived organizational support not significant on employee performance with c.r value0,587 ( 4) Leader member exchange positive interaction on employee performance withmediated affective commitment regression weight indirect effect 0,107. Management PTAdikencana Mahkotabuana Kebakkramat to increase of employee performance with focusleader member exchange, perceived organizational support and affective commitment.